NEGATIVE CAMPAIGNS IN SOCIAL MEDIA : A CASE OF #UnInstallTempo IN TWITTER PLATFORM - AMIR SODIKIN; JUNIARA JUWITA DWI UTARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Polarization on social media as a remain of the presidential election contestation at 2019 is still felt its impact. The supporters of both sides are confined in an algorithmic enclave. When the cover of Tempo magazine was seen as criticizing of President Jokowi, his supporters on social media were campaigned to attack Tempo. They mobilized the masses through the hashtag #UnInstallTempo. This emotional mobilization dropped the Tempo app's rating on the Google Play Store from 4.8 (scale 1-5) to 1.1 within 3 days. The Tempo attackers sought justification from fellow supporters without listening to Tempo's arguments. Finally, this condition actually gets a place in the eyes of citizens and Indonesian policy is not impossible nuanced mobocracy.